Designing and overproducing a tandem epitope of gp350/220 that shows a potential to become an EBV vaccine - Widodo; Nadya Veronica Margarecaesha Anyndita; Nurul Dluha; Muhaimin Rifa'i; Karimatul Himmah; Mulya Dwi Wahyuningsih (Heliyon, 2018)
Background: Epstein-Barr virus (EBV) can cause cancer in people from around the world. There is no EBV vaccine available for use on a global scale. However, emerging evidence suggests that the epitope on the gp350/220 capsid protein may be developed into an EBV vaccine. Nevertheless, the production of small, single epitope is challenging of stability issues and possible alteration of peptide structure. In this study, a tandem epitope was developed consisting of three single epitopes, aimed to improve stability, antigenicity and preserve epitope structure. Materials and methods: A tandem epitope was designed using bioinformatics based on the epitope structure of the gp350/220 protein. The tandem epitope structure was analyzed using a protein folding method with Abalone software, which was further refined via YASARA force field and molecular repairing using a FoldX method. Immunogenicity was examined with Epitopia software, whereas allergen properties were tested using AlgPred. The pattern of the tandem epitope binding with anti-gp350/220 antibodies was performed using Z-dock and snugDock. The tandem epitope was then overproduced in E. coli strain BL21 as a host cell. Result: Our model demonstrated a successfully designed and overproduced tandem epitope. The tandem epitope demonstrated a similar structure compared with the epitope of whole protein gp350/220. Our epitope also demonstrated non-allergen and antigenicity properties, and possessed antibody binding patterns consistent with whole protein gp350/220. Conclusion and recommendation: These data suggest a novel tandem epitope composed of three similar epitopes demonstrates antigenicity, structure, and binding properties consistent with whole protein gp350/220. We also demonstrate successful production of the tandem epitope using E. coli strain BL21 as a host. Future in vivo experimental animal research is necessary to test the ability of this tandem epitope to stimulate antibody production.